Efficiency Improvements through Combined Heat and Power for On-site Distributed Generation Technologies - Karki, Shankar; Kulkarni, Manohar; Mann, Michael D.; Salehfar, Hossein (Distributed Generation & Alternative Energy Journal, 2007)
With the evolution of electricity market transformation, there is a renewed interest in distributed generation (DG)—that has a promising role for mitigating technical, regulatory, and environmental constraints in the electricity sector. These bene fits are further enhanced with the ability of such DG in heat recovery applications in which the waste heat is used to produce hot water, heat building space, drive absorption cool- ing, and supply other thermal energy needs in a commercial building or industrial process. This article identi fies the ef ficiency gain and other environmental and economical bene fits of using fossil fuel based DG under combined heat and power (CHP) application. Based on emission factors and operational performance of existing commercially available DG under both separate heat and power (SHP) and CHP applications, economic and environmental performance of such DG is analyzed and compared under different loading conditions characterized by different heat to power (HPR) ratios